Alternative Oxidase Gene Family in Hypericum perforatum L.: Characterization and Expression at the Post-germinative Phase - Velada, Isabel; Cardoso, Hélia G.; Ragonezi, Carla; Nogales, Amaia; Ferreira, Alexandre; Valadas, Vera; Arnholdt-Schmitt, Birgit (Frontiers in Plant Science, 2016)
Alternative oxidase (AOX) protein is located in the inner mitochondrial membrane and is encoded in the nuclear genome being involved in plant response upon diversity of environmental stresses and also in normal plant growth and development. Here we report the characterization of the AOX gene family of Hypericum perforatum L. Two AOX genes were identified, both with a structure of four exons (HpAOX1, acc. KU674355 and HpAOX2, acc. KU674356). High variability was found at the N-terminal region of the protein coincident with the high variability identified at the mitochondrial transit peptide. In silico analysis of regulatory elements located at intronic regions identified putative sequences coding for miRNA precursors and trace elements of a transposon. Simple sequence repeats were also identified. Additionally, the mRNA levels for the HpAOX1 and HpAOX2, along with the ones for the HpGAPA and the HpCAT1, were evaluated during the post-germinative development. The gene expression analysis was performed by RT-qPCR with accurate data normalization, pointing out HpHYP1 and HpH2A as the most suitable RGs according to GeNorm algorithm. The HpAOX2 transcript demonstrated larger stability during the process with a slight down-regulation in its expression. Contrarily, HpAOX1 and HpGAPA (the corresponding protein is homolog to the chloroplast isoform involved in the photosynthetic carbon assimilation in other species) transcripts showed a marked increase, with a similar expression pattern between them, during the post-germinative development. On the other hand, the HpCAT1 (the corresponding protein is homolog to the major H2O2-scavenging enzyme in other species) transcripts showed an opposite behavior with a down-regulation during the process. In summary, our findings, although preliminary, highlight the importance to investigate in more detail the participation of AOX genes during the post-germinative development in Hypericum, in order to explore their functional role in optimizing photosynthesis and in the control of ROS levels during the process.